Research on China's Rural Development Strategy Based on SWOT-AHP Analysis (International Research in Economics and Finance, 2019)
The rapid urbanization development has helped China's economy to rise sharply, and it has also plunged the countryside into a development dilemma. Based on a questionnaire survey of 25 industry experts, this paper uses SWOT-AHP analysis to study the advantages, disadvantages, opportunities and threats of rural development, and finally determines the development strategy of rural China. Put forward three suggestions on rural development in China, that is, grasp the national strategic opportunity to develop modern agriculture, upgrade the level of rural human capital and cultivate the concept of ecological civilization.